Using one-way analysis of variance in the stochastic determinated design of experiment - Fomin, V.N.; Dik, A.V. (KSU Publ., 2015)
The possibility of using one-way dispersion analysis ANOVA in this article is discribed, for the evaluation of statistical significance of the empirical dependensis which was gift by using of stochastic determinated design of experiments (SDDE). It is shown that use of ANOWA can disambiguate the interpretation of some results.
Тəжірибені болжам-детерминирленген жоспарлау шеңберінде бірфакторлы дисперсиялық талдауды пайдалану
Использование однофакторного дисперсионного анализа в рамках вероятностно-детерминированного планирования эксперимента
Keywords: ANOWA; stochastic determinated design of experiment; regression analysis, analysis of variance; factor experiment